PENGARUH ARUS KAS AKTIFITAS OPERASI, INVESTASI, PENDANAAN DAN LABA PERUSAHAAN TERHADAP HARGA SAHAM DI BURSA EFEK INDDONESIA PERIODE 2009-2012 - Dompas, Saartje (JBE (Journal of Business and Economics), 2014)
This research aims to investigate the significance of cash flow from operating, investing and financing activities and earnings toward stock performance during 2009-2012.  Data is taken from income statement, statement of cash flows as well as stock price of manufacturing companies.  Indonesian manufacturing sector has four sub-sector namely food and beverages, pharmacy, cosmetics and household equipment.  To test the significant of ach variable of 32 companies as sample, this research employs multiple linear regressions.  The findings of this research show that cash flow from operations, investment and financing activities and earnings significantly affect stock price.  The coefficient of earnings is the greatest followed by coefficient of cash flow from operation, the investing and financing activities is the least.  R-squared of this model is 68%.